Effect of a Point Mutation in mprF on Susceptibility to Daptomycin, Vancomycin, and Oxacillin in an MRSA Clinical Strain - Chen, Feng-Jui; Lauderdale, Tsai-Ling; Lee, Chen-Hsiang; Hsu, Yu-Chieh; Huang, I-Wen; Hsu, Pei-Chi; Yang, Chung-Shi (Frontiers in Microbiology, 2018)
We previously reported the sequential recovery of daptomycin-nonsusceptible MRSA clinical isolates with an L431F substitution in the MprF protein. The aim of the present study is to determine the effect of this mutation by replacing the mprF gene on the chromosome of a daptomycin-susceptible progenitor strain, CGK5, to obtain CGK5mut having the L431F MprF mutation. Compared to CGK5, the daptomycin and vancomycin MICs of CGK5mut increased from 0.5 to 3 μg/ml and from 1.5 to 3 μg/ml, respectively; however, its oxacillin MIC decreased from 128 to 1 μg/ml in medium without added 2% NaCl. The expression levels of vraSR and several other cell-wall synthesis-related genes were significantly increased in CGK5mut, and the mutant also had significantly reduced negative cell membrane charge, thicker cell wall, and longer doubling time. These features were abolished in the reverse mutant carrying F431L MprF, confirming the pleiotropic effects of the L431F MprF mutation. We believe that this is the first work that shows a single MprF missense mutation can lead to not only changes in the cell membrane but also increased expression of vraSR and subsequently increased resistance to daptomycin and vancomycin while simultaneously conferring increased susceptibility to oxacillin in an isogenic MRSA strain.